A scent shield to survive: identification of the repellent compounds secreted by the male offspring of the cuckoo bumblebee Bombus vestalis. Issue 3 (21st November 2015) - Lhomme, Patrick; Ayasse, Manfred; Valterová, Irena; Lecocq, Thomas; Rasmont, Pierre
Abstract: In social insects, the high cost of parental investment has promoted the evolution of traits that reduce or avoid care for unrelated offspring. They have evolved a sophisticated recognition system which enables them to reject foreign individuals, and therefore prevent their nest's exploitation by parasites and predators. Nonetheless, many social parasites are able to overcome social insect recognition and parasitize their parental care behaviour by laying their eggs in host nests. Although several studies have already been conducted on the strategies used by social parasites to successfully invade host nests, the strategy used by its offspring to evade host rejection is still poorly understood. In bumblebees, previous investigations indicated that male offspring of Bombus vestalis (Geoffroy) (Hymeno‐ptera: Apidae), the specific obligate social parasite of Bombus terrestris (L.), may use allomones to evade host worker attacks. Following these studies, we performed electrophysiological studies and behavioural experiments to identify the potential repellents. Six compounds elicited electroantennographic responses in host worker antennae. The corresponding mixture of synthetic volatiles as well as pure tetradecyl acetate, and to a lesser extent pure ( Z )‐11‐hexadecenyl acetate, showed a repellent effect on starved host workers in a feeding bioassay. We hypothesize that tetradecyl acetate has a key function in the repellent effect of the secretions of B. vestalis male offspring towards B. terrestris host workers.